Philological and historical commentary on Ammianus Marcellinus XXVII - Boeft, J. den. (Philological and Historical Commentary on Ammianus Marcellinus, 2009)
Book 27 deals with events between 365 and 370. Military operations in the western and eastern half of the Empire take up a large part of the available space. Apart from military matters Ammianus deals with internal affairs. He discusses the terms of office of four Roman urban prefects and paints a picture of Petronius Probus, the mightiest civil official of the period. The most striking part of the book contains a portrait of the emperor Valentinian. This passage forms the centre of the book, which therefore has the structure of a triptych: of the two outer parts each contains military affairs in the West and the East and reports on some notable non-military events, whilst in the central panel Valentinian takes pride of place.